2003
DOI: 10.1007/s00125-003-1063-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant regulation of gene expression and neural tube development: Insights gained from diabetic pregnancy on molecular causes of neural tube defects

Abstract: Aims/hypothesis. Maternal diabetes increases oxidative stress in embryos. Maternal diabetes also inhibits expression of embryonic genes, most notably, Pax-3, which is required for neural tube closure. Here we tested the hypothesis that oxidative stress inhibits expression of Pax-3, thereby providing a molecular basis for neural tube defects induced by diabetic pregnancy. Methods. Maternal diabetes-induced oxidative stress was blocked with α-tocopherol (vitamin E), and oxidative stress was induced with the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
178
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(188 citation statements)
references
References 64 publications
8
178
0
2
Order By: Relevance
“…Antimycin A is a mitochondrial complex III inhibitor that stimulates superoxide production [40,41] and mimics the effects of maternal diabetes on Pax3 expression and NTD [39,47]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimycin A is a mitochondrial complex III inhibitor that stimulates superoxide production [40,41] and mimics the effects of maternal diabetes on Pax3 expression and NTD [39,47]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Non-diabetic Glut2 +/− male and female mice were mated and hyperglycaemia or oxidative stress was induced on day 7.5 as described previously [34,39]. Briefly, transient hyperglycaemia was induced by injecting 2 ml of 12.5% glucose-PBS solution subcutaneously approximately every 1-2 h between 09.00 and 17.00 h. Blood glucose concentrations were checked hourly, and animals were re-injected as needed to maintain the blood glucose concentration ≥300 mg/dl (16.65 mmol/l).…”
Section: Methodsmentioning
confidence: 99%
“…The congenital malformations associated with diabetic pregnancy affect many major organs, including the central nervous, cardiovascular, gastrointestinal, urogenital and musculoskeletal systems [5,6]. The pathogenesis of congenital anomalies is complex and still poorly understood, although it has been suggested that excessive reactive oxygen species (ROS) associated with hyperglycaemia are responsible for the increased risk of malformation [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the oxidative stress caused by hyperglycemia has been shown to disrupt the expression of genes such as Pax3 that is involved in neural tube formation which explains in part that hyperglycemia-induced oxidative stress alters gene expression leading to NTD [32] . Hyperglycemia-induced birth defects are attributed to the excessive production of reactive oxygen species (ROS) which has been shown to cause oxidative stress and subsequently increase the risk for fetal malformations [33,34] . Administration of antioxidants such as vitamin E and overexpression of ROS scavenging enzymes such as superoxide dismutase have been shown to prevent or reduce the risk for diabetic malformations in several animal studies although the exact mechanism is unknown [35][36][37][38][39][40] .…”
Section: Characterisation Of Metabolic Pathways In Ntdsmentioning
confidence: 99%